A review of an international sustainability standard (GlobalGAP) and its local replica (MyGAP) - Tey, Yeong Sheng; Rajendran, Natasha; Brindal, Mark; Ahmad Sidique, Shaufique Fahmi; Shamsudin, Mad Nasir; Radam, Alias; Abdul Hadi, Ahmad Hanis Izani (SAGE Publications, 2016)
In light of growing concerns about sustainable development, international sustainability standards are prevalent and are replicated by local governments to form country-specific sustainability standards. A consensus has been reached that local sustainability standards can be considered to underperform in view of their limited adoption. Supplementing the current literature, this study hypothesizes additional explanations of this phenomenon through a review of both the GlobalGAP (international) and Malaysian Good Agricultural Practices (MyGAP) standards. Through content analysis, the findings indicate that MyGAP provides a weak institutional framework and market opportunity structure. In addition, since it lacks transparency and accountability, its credibility is questionable. Although it is not clear whether such a credibility issue has a direct impact on the local market, sustainable produce is neither differentiated nor rewarded through premiums. The GlobalGAP standard was found to be an exemplar, and potential improvements are suggested to help support local sustainability standards.